ESPGHAN Committee on Nutrition Position Paper. Intravenous Lipid Emulsions and Risk of Hepatotoxicity in Infants and Children: a Systematic Review and Meta-analysis. Issue 5 (May 2016) - Hojsak, Iva; Colomb, Virginie; Braegger, Christian; Bronsky, Jiri; Campoy, Cristina; Domellöf, Magnus; Embleton, Nicholas; Fidler Mis, Nataša; Hulst, Jessie M.; Indrio, Flavia; Lapillonne, Alexandre; Mihatsch, Walter; et al.
Abstract : Supplemental Digital Content is available in the text Abstract : ABSTRACT: The aim of the present article was to perform a systematic review with meta-analysis of available scientific evidence regarding the role of different intravenous lipid emulsions (ILE) in the pathogenesis of cholestasis and parenteral nutrition–associated liver disease. A systematic review of the literature (up to March 2015) identified 23 randomized controlled trials (RCTs). Of these, 17 were performed in preterm infants or critically ill neonates with a short duration of intervention, 2 in older children with short-term use (following surgery or bone marrow transplantation), 1 in neonates with long-term use, and 3 in infants and children receiving long-term parenteral nutrition (PN). Meta-analysis showed no differences in the rate of cholestasis or bilirubin levels associated with short-term use of different ILEs. Because of high heterogeneity of the long-term studies no meta-analysis could be performed. Available studies found that the use of multicomponent fish oil (FO)-containing ILE compared with pure soya bean oil (SO), ILE-reduced liver enzymes, and bilirubin levels in noncholestatic children on long-term PN and one other RCT found that FO-based ILE-reversed cholestasis in a proportion of patients. The ESPGHAN Committee on Nutrition concludes that there is no evidence of a difference in rates of cholestasis or bilirubin levels between different ILE for short-term use in neonates. The use of multicomponent FO-containing ILE may contribute to a decrease in total bilirubin levels in children with IF on prolonged PN. Well-designed RCTs are, however, lacking and long-term effects have not been determined.